Electrophysiologically Guided Multitarget Stereotactic Intractable Epilepsy Surgery in Patients with Complex Epileptic Systems (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: complex epileptic systems; intractable epilepsy; neurophysiologic guidance; psycho-emotional disturbances; stereotactic multitarget epilepsy surgery